Pengaruh Keselamatan Dan Kesehatan Kerja (K3) Dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Pada CV. Sumber Pinus Jaya Kediri - Reni Sela Puspita Sari; Ustadus Sholihin; Zulfia Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2023)
In Indonesia, furniture industry companies are starting to spread and develop rapidly. The furniture industry is an industry that processes raw materials or semi-finished materials into finished goods. In ever-increasing business competition, companies must be able to manage human resources well. This aims to increase employee work productivity. This research aims to determine the influence of Occupational Safety and Health (K3) and the Work Environment on employee work productivity at CV. Sumber Pinus Jaya Kediri. This research sample consisted of 42 employees. The sampling technique used was saturated sampling. This research uses a quantitative type of research because it leads to measurement methods and samples to test variables and hypotheses using SPSS version 25. The results of the research show that the results of the Occupational Safety and Health (K3) t test have a partially significant effect on Work Productivity by getting a sig value. 0.000 < 0.05. The work environment has a partially significant effect on work productivity with a sig. 0.000 < 0.05. Meanwhile, the F test results show that Occupational Safety and Health (K3) and the Work Environment have a significant simultaneous effect on employee work productivity at CV. Sumber Pinus Jaya Kediri with sig. 0.000 < 0.05.